Epidermal Invagination with Distinctive Cornoid Lamella: A Case Study of Porokeratosis in A Middle-Aged Male (Community Based Medical Journal, 2025)
Porokeratosis is a rare keratinization disorder with specific pathologic findings involving abnormally processed epidermal keratin and presenting with the cornoid lamella. The current case report involves a 38-year-old male patient, who was communicating with a cutaneous lesion on the back of his left side, which best illustrates this condition. A 0.8x0.5x0.4 cm full-thickness skin biopsy was subjected to histopathological examination that showed an intradermal epidermal invagination with hyperkeratosis and parakeratosis. The characteristic diagnostic feature, the cornoid lamella, was described; the granular layer near the parakeratotic column was reduced. Further observations were that basal melanocytes were increased in areas immediately adjacent to the arterialized vessels and perivascular accumulation of chronic inflammatory cells in the dermis, while granulomas or malignancy were absent. The case also demonstrated the role of histopathological examination in increasing diagnostic rates and the need for the integration of various management approaches. With the risks of malignant transformation reported, primarily to squamous cell carcinoma, the concept incorporates compliance with follow-up examinations, photoprotective interventions, patient counseling, and/or adapted therapy perspectives. The case also shows multi-factorial etiology of porokeratosis through the presence of both genetic mutations of MVK and MVD and environmental factors, and immunological state. This case study adds a rare evidence along with its specific histopathological characteristics that help to define porokeratosis and direct relevant therapeutic management.  CBMJ 2025 January: Vol. 14 No. 01 P: 168-171